What to Know About Medicines With New Active Ingredients Approved in FY 2016 / 2016 in Japan and EU: A Brief Comparison of New Medicines Approved in Japan and the EU in 2016. (March 2018) - Kondo, Hideyuki; Saint-Raymond, Agnès; Yasuda, Naoyuki
The Pharmaceuticals and Medical Devices Agency (PMDA) in Japan and the European Medicines Agency (EMA) have a long-standing experience of reviews of new medicines, and they meet their target pre-market review periods. In FY 2016 / 2016, 112 and 83 new medicines were approved in Japan and EU, respectively. Out of these medicines, 41 and 27 medicines containing new active ingredients were approved with total pre-market review periods of 209 days and 428 days in Japan and EU, respectively. Approximately one-third of these medicines were reviewed by the Agencies in close timing, within 1 year between pre-market review applications in Japan and in EU. Taking into account the increasing number of global clinical trials and constant number of consultations or scientific advice related to global clinical trials in Japan, it is clear that the importance of the continuous, collaborative relationship between EMA and PMDA is more and more crucial, as it does facilitate close and timely exchange of information and opinions on products and technologies under development. There already are effective collaborative frameworks between PMDA and EMA in addition to daily communication, and our findings support the development and best use of regulatory tools such as consultation services and scientific advice/protocol assistance for the benefit of the pharmaceutical industry but mostly of patients.